Robust Finite-time H∞Control of Linear Time-varying Delay Systems with Bounded Control via Riccati Equations - Piyapong Niamsup (2018)
© 2017, Institute of Automation, Chinese Academy of Sciences and Springer-Verlag GmbH Germany, part of Springer Nature. In this paper, we will present new results on robust finite-time H∞control for linear time-varying systems with both time-varying delay and bounded control. Delay-dependent sufficient conditions for robust finite-time stabilization and H∞control are first established to guarantee finite-time stability of the closed-loop system via solving Riccati differential equations. Applications to finite-time H∞control to a class of linear autonomous time-delay systems with bounded control are also discussed in this paper. Numerical examples are given to illustrate the effectiveness of the proposed method.